2020
DOI: 10.1038/s41598-020-67210-3
|View full text |Cite
|
Sign up to set email alerts
|

A Salt Tolerance Evaluation Method for Sunflower (Helianthus annuus L.) at the Seed Germination Stage

Abstract: Salinity is a major abiotic stress that affects plant growth and development and leads to crop yield loss. Many crop species are more sensitive to salinity stress at the seed germination stage than at other developmental stages. Some studies have shown that sunflower is tolerant to salinity to a certain degree. However, no systematic screening data for sunflower germplasms are available for salinity stress. In this study, 552 sunflower germplasms with different genetic backgrounds were evaluated for salt toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 33 publications
2
51
0
1
Order By: Relevance
“…As one of the most significant abiotic stresses influencing grain yield, salinity has become a great threat to agricultural sustainability, affecting more than 800 million hectares of land around the world [ 1 , 2 , 3 ]. Development of salt-tolerant cultivars is one of the most effective ways to deal with this issue [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the most significant abiotic stresses influencing grain yield, salinity has become a great threat to agricultural sustainability, affecting more than 800 million hectares of land around the world [ 1 , 2 , 3 ]. Development of salt-tolerant cultivars is one of the most effective ways to deal with this issue [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Screening wheat genotypes with salt tolerance has been inhibited by the lack of effective evaluation methods [ 2 , 4 , 19 ]. It is quite imperative to determine growth or physiological parameters as the tolerant index for the evaluation of abiotic stress tolerance [ 4 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is the third highest oilseed produced in the world, the fourth vegetable oil and the third protein feed source among oilseed crops. Although sunflower plants exhibit medium salt tolerance, their production is affected by high soil salinity, which is common in arid or semi-arid areas ( Karrenberg et al, 2006 ; Li et al, 2020 ). Understanding response to salinity in sunflowers and, in particular, the molecular basis of its salt tolerance mechanism is central to development of breeding and bioengineering strategies aimed to improve the salt tolerance in this species.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, NaCl toxicity is related to a long-term and non-specific disturbance of cellular osmotic, ionic, electric, redox and metabolic balance, inhibiting photosynthesis, respiration, growth, development and reproduction ( Shabala, 2013 ; Demidchik et al, 2014 , 2018 ; Negrão and Schmöckel, 2017 ; Isayenkov and Maathuis, 2019 ). It is generally accepted that Na + is more toxic than Cl − for most plant species ( Shabala, 2013 ; Flowers and Colmer, 2015 ), although the detrimental effect of Cl − should not be underestimated ( White and Broadley, 2003 ; Li et al, 2020 ). The key mechanisms of toxic Na + influx into the root cells is its entry through the plasma membrane-associated non-selective cation channels (NSCCs; Demidchik and Tester, 2002 ; Shabala et al, 2006 ; Demidchik and Maathuis, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, its tolerance to salt stress varies according to the genetic material. Li et al (2020) observed that out of 552 sunflower genotypes, only 30 were considered to be highly tolerant and 53 tolerant to salt in the germination phase under 300 mM NaCl. For the genotype H. annuus L. cv.…”
Section: Introductionmentioning
confidence: 99%